Peningkatan Peranan Keluarga dalam Upaya Pencegahan Penularan Tuberkulosis Paru di Desa Moncongloe Bulu Kabupaten Maros - Sudirman Efendi; Imran Pashar (Idea Pengabdian Masyarakat, 2023)
Tuberculosis (TB) is an infectious disease that often results in death. Every year millions of people continue to suffer from TB. Moncongloe  Village is a village where the prevalence rate of TB disease is quite high and one of the problems is related to knowledge. Therefore, the community service activity this time is to provide education about TB disease and an understanding of the importance of the role of the family in preventing transmission of TB disease. The method used through health counseling using leaflets, discussions or questions and answers. Apart from that, a blood pressure check and joint exercise were also carried out in the Moncongloe Bulu Village office hall, Maros Regency. The results of this activity are proven to be very much needed by the surrounding community who look very enthusiastic when given health education materials, so it is hoped that they will be able to provide additional references to the community